The Strategy of The International Business of The Chinese Company in The International Market - Xiaqing Li; Aleksandr Koberidze (Communications of International Proceedings, 2021)
This article discusses the main directions of China's international business in the international market: investment, infrastructure projects, lending. China occupies a leading position in the global economy and politics, and invests heavily in modernizing its economic potential and business tools. China has achieved significant results in the international arena thanks to the competent use of a complex of various mechanisms. Today we are witnessing how the whole world is undergoing a profound transformation, which implies the expansion of all the company's capabilities in using the results of information technology development. Such transformations undoubtedly open up great opportunities for all business owners in both national and international markets.
Keywords: economy; business; international market; chinese economy; strategy.